2012
DOI: 10.1371/journal.pone.0045180
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Responses to Chemical Stimulation of the Hypothalamic Arcuate Nucleus in the Rat: Role of the Hypothalamic Paraventricular Nucleus

Abstract: The mechanism of cardiovascular responses to chemical stimulation of the hypothalamic arcuate nucleus (ARCN) was studied in urethane-anesthetized adult male Wistar rats. At the baseline mean arterial pressure (BLMAP) close to normal, ARCN stimulation elicited decreases in MAP and sympathetic nerve activity (SNA). The decreases in MAP elicited by ARCN stimulation were attenuated by either gamma-aminobutyric acid (GABA), neuropeptide Y (NPY), or beta-endorphin receptor blockade in the ipsilateral hypothalamic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 56 publications
7
61
0
2
Order By: Relevance
“…In this and other series of experiments, the ARCN was always identified by microinjections of NMDA (10 mM), which elicited decreases in MAP (19 Ϯ 1 mmHg) and increases in HR (46 Ϯ 3 beats/min, n ϭ 9) in nonbarodenervated rats (26). Time intervals between the microinjection and beginning of the response (onset) and maximum response (peak) and the end of the response (duration) were noted.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…In this and other series of experiments, the ARCN was always identified by microinjections of NMDA (10 mM), which elicited decreases in MAP (19 Ϯ 1 mmHg) and increases in HR (46 Ϯ 3 beats/min, n ϭ 9) in nonbarodenervated rats (26). Time intervals between the microinjection and beginning of the response (onset) and maximum response (peak) and the end of the response (duration) were noted.…”
Section: Resultssupporting
confidence: 53%
“…We have recently shown that microinjections of N-methyl-D-aspartic acid (NMDA) into the ARCN elicited an increase in heart rate (HR) in rats regardless of whether the baroreceptors were intact or denervated (26,27,36). Tachycardic responses elicited from the ARCN are mediated via the release of glutamate and ␣-melanocyte-stimulating hormone (␣-MSH) in the hypothalamic paraventricular nucleus (PVN) because blockade of ionotropic glutamate receptors (iGLURs) and melanocortin 3/4 receptors in the ipsilateral PVN attenuated these responses (27).…”
mentioning
confidence: 99%
“…In the mouse DMH, we observed a significant number of RVLM-projecting neurons; however, the number was far smaller than when the CtB injections encompassed the raphe pallidus significant decreases in SNA, MAP, and HR, because NPY inhibits a G protein-activated inwardly rectifying K (GIRK) current (39-41), which can hyperpolarize to a greater extent than GABA A receptors, which open Cl channels. While the limited inhibition by GABA was expected, the effect of PVN AgRP on SNA in rats is controversial (8,42). Here, we show that doses of PVN AgRP that exceed those required to elicit food intake and sufficient to decrease body temperature failed to decrease SSNA, AP, or HR.…”
Section: Discussionmentioning
confidence: 69%
“…Based on anatomical evidence that PVN presympathetic neurons are richly innervated by ArcN NPY fibers in mice ( Figure 2) and rats (4), the strong sympathoinhibitory effects of NPY in the PVN in mice (Figure 3) and rats (4), and indirect evidence in rats that ArcN NPY neurons inhibit SNA via a synapse in the PVN (5,7,8), we were surprised that blockade of PVN NPY1R only weakly reversed the effects of select ArcN NPY/AgRP neuronal activation. In sharp contrast, blockade of DMH NPY1R completely reversed these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation